2012
DOI: 10.1542/peds.2012-0055e
|View full text |Cite
|
Sign up to set email alerts
|

Standard 2: Containing Risk of Bias

Abstract: DILEMMAThere is a crisis of credibility facing the child health research community because of the paucity of reliable estimates of the effects of interventions in children. Associations between risk of bias assessments and treatment effect estimates have important implications, for the clinician, and the families face important challenges as decisionmakers stemming from results that exaggerate treatment effectiveness or safety. Consequently, interventions that are not efficacious and potentially harmful may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Moreover, a recent standard, developed by the international organization StaR Child Health, for minimizing risk of bias in pediatric trials could be equally applied to any trial. [32] Consistent with Savovic et al’s findings, other features may be more salient in assessing possible bias such as choice of outcomes (subjective vs. objective).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, a recent standard, developed by the international organization StaR Child Health, for minimizing risk of bias in pediatric trials could be equally applied to any trial. [32] Consistent with Savovic et al’s findings, other features may be more salient in assessing possible bias such as choice of outcomes (subjective vs. objective).…”
Section: Discussionsupporting
confidence: 79%
“…In order to maximize credibility and familiarity, the wiki was established under the auspices of StaR Child Health, an international initiative dedicated to improving the quality of pediatric clinical research [38], and is available at www.starchildhealth-riskofbias.wikispaces.com. Specifically, the wiki was designed to contribute to the KT agenda of the StaR Child Health Risk of Bias Standard Development Group [39]. Content was structured to emphasize two main areas: risk of bias and the conduct of pediatric RCTs.…”
Section: Methodsmentioning
confidence: 99%
“…Demonstrating a specific strategy on information and recruitment is a prerequisite for a successful trial and even more so for children. The standard uses clinical scenarios to discuss and provide guidance on (1) who should give consent for children, (2) what information is necessary to obtain consent, (3) ensuring equitable opportunity rather than exploitation, (4) discusses the issue of payment and compensation, (5) the potential conflict of a child's clinician also acting as the investigator and (6) issues on eligibility of patients invited to participate in a trial. Containing risk of bias :18 A high risk of bias in a trial can lead to an overestimate of treatment effects13 and reviews of paediatric trials have shown that many are at a high risk of bias 14. This StaR paper addresses how to reduce and limit bias, such as ensuring adequate (1) techniques and security of randomisation, (2) blinding, (3) follow-up and handling of missing outcome data and (4) outcome reporting.…”
Section: The First Six Star Child Health Reportsmentioning
confidence: 99%
“…Containing risk of bias :18 A high risk of bias in a trial can lead to an overestimate of treatment effects13 and reviews of paediatric trials have shown that many are at a high risk of bias 14. This StaR paper addresses how to reduce and limit bias, such as ensuring adequate (1) techniques and security of randomisation, (2) blinding, (3) follow-up and handling of missing outcome data and (4) outcome reporting.…”
Section: The First Six Star Child Health Reportsmentioning
confidence: 99%